The Effects of Price Perception and Product Quality on Repurchase Intention: The Mediating Role of Customer Satisfaction Among Consumers of Make Over Lipstick in Cimahi City - Wan Maharani Alista Sari; Leni Evangalista Marliani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of price perception and product quality on repurchase intention, with consumer satisfaction as a mediating variable among Make Over lipstick consumers in Cimahi City. A quantitative approach was employed, utilizing an explanatory research design and survey method. The sample consisted of 134 female consumers who had purchased and used Make Over lipstick, selected through convenience sampling. Data were collected using a five-point Likert scale questionnaire and analyzed with descriptive analysis, multiple linear regression, path analysis, and the Sobel test, assisted by SPSS version 25. The results indicate that price perception does not have a significant effect on consumer satisfaction, whereas product quality has a positive and significant effect on consumer satisfaction. Perceived price, product quality, and consumer satisfaction each have a positive and significant effect on repurchase intention, with perceived price exerting the most dominant direct influence. Mediation analysis indicates that consumer satisfaction does not mediate the effect of perceived price on repurchase intention, but does mediate the effect of product quality on repurchase intention. These findings suggest that appropriate price management and product quality improvement are necessary to enhance consumer satisfaction and repurchase intention for Make Over lipstick.